Factors influencing antiretroviral treatment suboptimal adherence among perinatally hivinfected adolescents in Thailand - Luyi Xu (2018)
© 2017 Xu et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: Existing studies have suggested decreased adherence and rebound in mortality in perinatally HIV-infected adolescents receiving antiretroviral therapy (ART) as compared to adults and young children. Methods: We used both quantitative and qualitative approaches to identify factors influencing adherence among perinatally infected adolescents in Thailand. We analyzed data from 568 pairs of perinatally infected adolescents (aged 12-19) and their primary caregivers in the Teens Living With Antiretrovirals (TEEWA) study, a cross-sectional survey conducted in 2010-2012. We also conducted 12 in-depth interviews in 2014 with infected adolescents or their primary caregivers to elicit experiences of living with long-term ART. Results: From the quantitative analysis, a total of 275 (48. 4%) adolescents had evidence of suboptimal adherence based on this composite outcome: adolescents self-reported mi ssing doses in the past 7 days, caregiver rating of overall adherence as suboptimal, or latest HIV-RNA viral load ≥1000 copies/ml. In multivariate logistic regression analysis, younger age, having grandparents or extended family members as the primary caregiver, caregiver-assessed poor intellectual ability, having a boy/girlfriend, frequent online chatting, self-reported unhappiness and easiness in asking doctors questions were significantly associated with suboptimal adherence. From the in-depth interviews, tensed relationships with caregivers, forgetfulness due to busy schedules, and fear of disclosing HIV status to others, especially boy/girlfriends, were important contributors to suboptimal adherence. Social and emotional support and counseling from peer group was consistently reported as a strong adherencepromoting factor. Conclusion: Our findings highlight unique barriers of ART adherence among the perinatally infected adolescents. Future interventions should be targeted at helping adolescents to improve interpersonal relationships and build adaptive skills in recognizing and addressing challenging situations related to ART taking.